2008
DOI: 10.1128/mcb.00244-08
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of Human AP-Endonuclease (APE1/Ref-1) in YB-1-Mediated Activation of the Multidrug Resistance Gene MDR1

Abstract: The mammalian AP-endonuclease APE1 is a ubiquitous and remarkably multifunctional protein. It plays a central role in the base excision repair (BER) pathway for repairing damaged bases and DNA single-strand breaks induced by reactive oxygen species and alkylating agents and also repairing AP sites that are generated spontaneously or after the excision of oxidized and alkylated bases by DNA glycosylases (12,40). APE1 was also shown to incise DNA 5Ј to oxidatively damaged bases including 5,6-dihydrothymidine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(152 citation statements)
references
References 57 publications
7
144
0
1
Order By: Relevance
“…Furthermore, the in vivo involvement of APE1 in RNA metabolic pathways was further corroborated by the observation of the APE1 association, through its N-terminal domain, with rRNA and the ribosome processing protein NPM1 within nucleoli (149). Furthermore, APE1 has been shown to interact with factors involved in the splicing process, such as the heterogeneous nuclear ribonucleoprotein L (81) [which is a key regulator of splicing that binds CA repeats with high affinity (65)], YB-1 (29,119), as well as with proteins involved in the ribosome assembly and RNA maturation within cytoplasm (149).…”
Section: Fig 5 Schematic Representationmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, the in vivo involvement of APE1 in RNA metabolic pathways was further corroborated by the observation of the APE1 association, through its N-terminal domain, with rRNA and the ribosome processing protein NPM1 within nucleoli (149). Furthermore, APE1 has been shown to interact with factors involved in the splicing process, such as the heterogeneous nuclear ribonucleoprotein L (81) [which is a key regulator of splicing that binds CA repeats with high affinity (65)], YB-1 (29,119), as well as with proteins involved in the ribosome assembly and RNA maturation within cytoplasm (149).…”
Section: Fig 5 Schematic Representationmentioning
confidence: 87%
“…Actually, several noncanonical factors have been demonstrated to participate BER, even though their in vivo functions are yet to be fully unraveled. The list of non-BER proteins includes for instance: YB-1 [which has been shown to interact with the endonuclease VIII-like 2 (NEIL2) glycosylase (35), the endonuclease III-like glycosylase (NTH1) and APE1 (29)], NEIL2 [which was also found to interact with the RNA-binding protein hnRNP-U (6)], HMGB1 [which has been implicated in single-strand break (SSB) repair involving Polb (90)] and the tumor suppressor p53, which was also shown to play a role in DNA damage repair through direct binding to APE1 and Polb (168). The list of these non-BER proteins is still growing, supporting the notion that BER in vivo is far more complex than the simple model that we can reconstitute in vitro.…”
Section: Relevance Of the Unfolded Domains In Ber Proteinsmentioning
confidence: 99%
“…APE1 is also known as redox effector factor 1 (Ref1), as it affects the redox status of, among other proteins, many TFs. APE1/Ref1 and YB-1 directly interact, 110 they bind the MDR1 core promoter and removal of APE1 leads to decreased YB-1, Pol II and p300 promoter association in ChIP assays. 111 This led the authors to propose that the YB-1/CCAAT interaction mediates the recruitment of the APE1/p300/Pol II complex onto the promoter.…”
Section: Nf-y Is the Sequence-specific Ccaat Factormentioning
confidence: 99%
“…Thus, APE1 may be required for oxidative DNA lesion processing or for a more general stress response. Moreover, Chattopadhyay et al (25) have reported that acetylated APE1, through an interaction with the transcription factor YB-1, can activate expression of the multi-drug resistance gene MDR1. Increased levels of the MDR1 P-glycoprotein membrane transporter are associated with enhanced drug efflux and resistance in cancer cells, and could explain the sensitizing effect of APE1 depletion to compounds such as cisplatin.…”
Section: Protein Depletionmentioning
confidence: 99%